Cost-effectiveness of the SMILE intervention compared with usual care for people with severe mental illness: A randomized clinical trial - Mohamed El Alili; Berno van Meijel; Maurits W. van Tulder; Marcel Adriaanse (PLoS ONE, 2025)
Objectives Only studying effectiveness of lifestyle interventions for people with severe mental illness (SMI) is insufficient for policy making. As budgets for healthcare are limited, policy makers face the problem of allocating scarce healthcare resources. Cost-effectiveness studies are needed, but currently cost-effectiveness studies of lifestyle interventions for people with SMI delivered in ambulatory care are limited. The aim of this current study was to evaluate the cost-effectiveness of a lifestyle intervention for people with SMI living in the Dutch community in comparison with usual care. Methods and findings An economic evaluation was performed using a societal perspective alongside the Severe Mental Illness Lifestyle Evaluation (SMILE) pragmatic cluster randomized controlled trial. The SMILE lifestyle intervention is a one-year, group-based intervention delivered by trained mental healthcare workers. Costs, body weight change and quality of life were assessed at baseline, 6 and 12 months. Mixed models were used to estimate incremental costs and effects between the treatment group and the usual care group. Overall, the SMILE intervention resulted in lower total costs compared to the usual care group (-€719, 95% CI -7133; 3897). The effect difference between the intervention and usual care groups was -3.76 (95% CI -6.30; -1.23) kilograms for body weight and -0.037 (95% CI -0.083; 0.010) for QALYs. Conclusions Overall, the SMILE intervention resulted in lower total costs compared to the usual care group and was cost-effective for body weight change. However, the SMILE intervention does not seem cost-effective with regards to QALYs. More cost-effectiveness studies in other countries and other settings are needed to gain further insight into the cost-effectiveness of lifestyle interventions for people with SMI.